2009
DOI: 10.1007/s00542-009-0825-2
|View full text |Cite
|
Sign up to set email alerts
|

Linear and non-linear behavior of mechanical resonators for optimized inertial electromagnetic microgenerators

Abstract: In this work, the design, fabrication and characterization of an electromagnetic inertial microgenerator compatible with Si micro-systems technology is presented. The device includes a fixed micromachined coil and a movable magnet mounted on a resonant polymeric structure. The characterization of the fabricated prototypes has allowed to observe the presence of non linear effects that lead to the appearance of hysteretic vibrational phenomenon. These effects are likely related to the mechanical characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Moreover, the wound coil-type EMPGs have lesser prospect in being integrated into the planar micro fabrication processes. The planar coil-type EMPGs [5,11,13,14,18,27,28,30] mostly have less coil resistance but produce low output voltages (<180 mV) and will need a special ULV rectifier and multiplier circuit for practical usage.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the wound coil-type EMPGs have lesser prospect in being integrated into the planar micro fabrication processes. The planar coil-type EMPGs [5,11,13,14,18,27,28,30] mostly have less coil resistance but produce low output voltages (<180 mV) and will need a special ULV rectifier and multiplier circuit for practical usage.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…The authors reported a 40 mV voltage amplitude and 100 μW power generation at the excitation frequency of 60 Hz. A membranetype EMPG, containing a 127 μm thick kapton membrane to support NdFeB magnets, that moves within a recess provided in a silicon wafer (wafer 1), and within a printed circuit board (PCB) frame (wafer 2) has been reported by Serre et al [14]. The recess is produced by bulk micro-machining.…”
Section: Moving Magnet Empgsmentioning
confidence: 99%
“…The geometry of the coil for optimization of the electromagnetic coupling in the devices by ANSYS was described and proposed in publications (Christophe et al 2008;Benasciutti et al 2010). Two-stage procedure (lumped-parameter simulation and magneto-static finite element simulation) was clarified in publications (Buren and Troster 2007;Serre et al 2009), where mechanical resonance frequency and load resistance are optimized regarding maximum output power. Taguchi optimization strategy was presented in publication (Baekho et al 2007) and papers (Messine et al 1998;Song et al 2009) present other deterministic methods.…”
Section: Optimization Methods For Development Of Energy Harvesting Apmentioning
confidence: 99%
“…Both rigid PCB made of FR-4 boards [13][14][15][16] and flexible PCB made of polyimide (PI) films [17,18] have been used to fabricate energy harvesters. In [13], resonant structures such as cantilever beams were fabricated in FR-4 boards, and magnets were attached to the resonant structures as mass.…”
Section: Introductionmentioning
confidence: 99%